The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1992
DOI: 10.2135/cropsci1992.0011183x003200030039x
|View full text |Cite
|
Sign up to set email alerts
|

Adaptation to Midseason Drought of Cowpea Genotypes with Contrasting Senescene Traits

Abstract: Monocarpic senescence traits may influence adaptation to midseason drought by their effects on drought escape and dehydration avoidance. Adaptive attributes of two related cowpea [Vigna unguiculata (L.) Walp.] genotypes, contrasting in monocarpic leaf senescence, were evaluated under well‐watered and drought treatments in the field. Drought stress was imposed during flowering and pod filling for 19 consecutive days before irrigation was resumed. Delayed leaf senescence was expressed by genotype 8517 under both… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
31
0
5

Year Published

1997
1997
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(40 citation statements)
references
References 0 publications
4
31
0
5
Order By: Relevance
“…The drought stress treatment did not receive water for 20 days [21] after stress induction while the non-stress treatment received water twice a week until physiological maturity.…”
Section: Treatmentsmentioning
confidence: 99%
See 1 more Smart Citation
“…The drought stress treatment did not receive water for 20 days [21] after stress induction while the non-stress treatment received water twice a week until physiological maturity.…”
Section: Treatmentsmentioning
confidence: 99%
“…Brazil 5, NE 45 and NE 50 experienced a seed yield reduction of 83% and 36% respectively under soil moisture stress while WC 8, MU24C, Secow 5T, Secow 3B, MU15, IT84 and Secow 4w gave relatively higher yields. [21] reported that the reduction in seed yield under water stress was associated with the decrease in yield components such as number of pods per plant and number of seeds per pod. Cowpea …”
Section: Yield and Its Components Indicators Of Drought Tolerance At mentioning
confidence: 99%
“…The types are able to flower and mature before the on-set of mid-season moisture stress, thus escaping drought. Among tropical legumes, short-duration cultivars have been developed for cowpea (Gwathmey and Hall 1992;Hall and Patel 1992;Mligo and Singh 2006) and pigeonpea (Gwata and Siambi 2009;Silim and Omanga 2001). Short-duration cowpeas that can attain 2.0 t/ha within 60 to 70 d after planting have been reported (Ehlers and Hall 1997).…”
Section: Use Of Short-duration Cropsmentioning
confidence: 99%
“…Certains ont porté sur l'appréciation de critères morpho-physiologiques tels que la taille et / ou le nombre de certains organes (longueur de l'épicotyle, longueur de la racine, surface foliaire, circonférence au collet, nombre de gousses, masse de matières sèches de feuilles ou de graines, biomasse totale, etc.) (Hall et Grantz, 1981 ;Gwathmey et Hall, 1992 ;Sarr et al, 2001 ;Ogbonnaya et al, 2003 ;Badiane et al, 2004). D'autres ont porté sur l'efficience d'utilisation de l'eau des plantes (Hall et al, 1990 ;Hall et al, 1994), ou se sont intéressés à la régulation des systèmes enzymatiques impliqués dans la détoxification des déchets métaboliques tels que les espèces actives de l'oxygène issus de la déshydratation des plantes (Brou et al, 1998).…”
Section: Introductionunclassified
“…L'étude des réponses de ces plantes au déficit hydrique sur la base des p aram ètres physiologiques dérivant des échanges gazeux sont également nombreux (Schulze et Hall, 1982 ;Gwathmey et Hall, 1992 ;Tuba et al, 1996). Ceci est lié au fait que les effets du stress hydrique sur la photosynthèse des plantes s'observent de façon spectaculaire au niveau des échanges gazeux.…”
Section: Introductionunclassified